Pressure on the Electrode to Reduce Discomfort During Neuromuscular Electrical Stimulation in Individuals With Different Subcutaneous-Fat Thickness: Is the Procedure Effective and Reliable? - Raphael Luiz Sakugawa; Lucas B. R. Orssatto; Lucas T. Sampaio; Heiliane de Brito Fontana; Fernando Diefenthaeler (IEEE, 2022)
The addition of manual pressure on the electrode during neuromuscular electrical stimulation (NMES) has been used to reduce current intensity and perceived discomfort. In this study we aimed to test i) whether this approach affect the reliability of commonly made torque output measurements and ii) whether subcutaneous-fat thickness influence the efficacy of this approach in reducing current intensity and perceived discomfort. Twenty-one men (24 ± 3.1 years) performed knee extension maximal voluntary isometric contractions with and without manual pressure on the NMES femoral nerve electrode (superimposed and resting doublets, 2 pulses at 100 Hz) during two separate sessions. Torque output was measured in an isokinetic dynamometer and thigh subcutaneous-fat thickness assessed with ultrasonography. A scale of perceived discomfort was presented after contractions. Reductions in current intensity ( ${p} < 0.001$ ) and discomfort during superimposed doublet ( ${p}=0.002$ ) and resting doublet ( ${p}=0.002$ ) were confirmed for the condition in which pressure was applied to the electrode. Fat thickness was correlated to changes in current intensity (r = 0.63; ${p}$ = 0.002) and changes in discomfort (r = 0.45; ${p}$ = 0.04) and no differences between pressure conditions and testing sessions were observed for torque output ( ${p}$ > 0.05; ICC 0.95). Adding manual pressure during NMES on femoral nerve reduces discomfort and the maximal NMES intensity required to reach maximum torque without affecting torque output magnitude and reliability. Greater reduction in intensity and discomfort were observed in participants with higher subcutaneous-fat thickness levels after adding pressure on the electrode.